Determinants Of Behavioural Intention And Usage Of Information And Communications Technology-Enhanced Student Centered Teaching Methods Among Accounting Lecturers In Malaysian Public Universities - Leow, Lei Ping (2018)
The study explores the factors influencing behavioural intention and usage of Information and Communications Technology (ICT)-enhanced student centered teaching acceptance and usage among Malaysian public universities’ accounting lectures. Existing literature in teaching innovation has identified teachers’ perceptions and reactions as the key barriers in its design and implementation success, but not much information is available on these antecedents as most existing studies prefer to focus on investigating the outcomes. Underpinned by the Unified Theory of Acceptance and Use of Technology (UTAUT) model, this study examines the effects of performance expectancy and effort expectancy on accounting lecturers’ behavioural intention to increase the usage of ICT-enhanced student centered teaching methods in voluntary setting. It also investigates the effects of facilitating conditions and the resulting behavioural intention on the usage of ICT-enhanced SCL teaching methods. Additionally, this study extends the UTAUT model by substituting the social influence factor in the original model into more comprehensive coercive, normative and mimetic pressures based on the unique contexts of Malaysia’s accounting education. Following the calls of Hala Tuju reports, it also seeks to verify the existence of a direct relationship between personal characteristics (namely highest academic qualification, teaching experience and industry experience) and usage in the UTAUT model.